The The association between Vitamin D serum level and sleep quality among pregnant women in Asia: A Systematic Review - Faustine, Gredel; Kurniawan, Felicia; Regina (Universitas Udayana, 2024)
Background and purpose: Studies have investigated that Vitamin D serum level is associated with sleep quality and circadian rhythms in pregnant women in Asia, but the results remained controversial. This systematic review is conducted to explore the association between Vitamin D serum level and sleep quality among pregnant women population in Asia. Methods: We conducted systematic literature review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Relevant studies that discussed the association between Vitamin D serum level and sleep quality was retrieved from Pubmed, EBSCO, and Proquest. The outcome variable was sleep-quality which measured with Pittsburg Sleep Quality Index (PSQI) questionnaires and the independent variable was the serum 25(OH)D levels. A total 2,285 articles were excluded, leaving 3 final articles to be analyzed. The risk of bias was assessed with the New-Castle Ottawa Quality Assessment Scale (NOS). Results: Three studies included in this review with a total of 1,359 pregnant women in Asia, ranging from 18 to 68 years old. All three studies were controlled for covariates. Out of three studies, two studies showed a significant result of the association between Vitamin D serum level with sleep quality with a p-value <0,05. Causal reasons remained unexplained considering the studies were completed in cross-sectional and cohort design. Conclusion: This study gives an overview of the role of Vitamin D in the sleep quality of pregnant women in Asia. Future research should focus on conducting more comprehensive studies with stringent criteria to further explore this association in diverse Asian populations